Modeling and Analysis of Real Time Fixed Priority Scheduling using UML 2.0 - Hazra, Rumpa; Dey, Shouvik; Kanjilal, Ananya; Bhattacharya, Swapan (INFOCOMP Journal of Computer Science, 2013)
Real Time Systems (RTS) interact with their environments using time constrained input/output signals. A functional misbehavior or a deviation from the specified time constraints may have catastrophic consequences. Hence, ensuring the correctness of such systems is extremely important and necessary. The increasing complexities of now-a-days ubiquitous real time systems require using an adequate modeling language. Unified Modeling Language (UML), a widely used visual object oriented modeling language, has proved to be effective and suitable for real time systems. The paper discusses the ability of UML and its profile to determine the schedulability of a fixed priority real time system. This paper puts stresses on the occurrence of deadlock in using the Priority Inheritance Protocol and prevention of such using the Priority Ceiling Protocol. Using UML 2.0 Sequence and Timing Diagrams, we model these two protocols and further, we analyze and compare these models.